Low temperature complete combustion of dilute toluene and methyl ethyl ketone over Mn-doped ZrO2 (cubic) catalysts - Choudhary, Vasant R.; Deshmukh, G. M.; Pataskar, S. G. (Journal of Chemical Technology and Biotechnology, 2005)
Combustion of dilute toluene and methyl ethyl ketone over Mn-doped ZrO2 catalysts prepared using different precipitating agents, such as tetra-alkyl ammonium hydroxides and NH4OH, having Mn/Zr ratios from 0.05 to 0.67, and calcined at different temperatures has been thoroughly investigated. The Mn-doped ZrO2 catalyst shows high toluene or methyl ethyl ketone combustion activity, particularly when its ZrO2 is in cubic form, when its Mn/Zr ratio is close to 0.2, and when it is prepared using tetra-methyl ammonium hydroxide as a precipitating agent and calcined at 773 K. (c) 2005 Society of Chemical Industry.
Keywords: combustion of methyl ethyl ketone; combustion of toluene; Mn-doped ZrO2 catalyst